Моделирование многокомпонентных сигналов в хронопотенциометрии - Суровцев, И.В. (Кибернетика и вычислительная техника, 2016)
Впервые описан метод моделирования многокомпонентных сигналов при измерении концентрации химических элементов в хронопотенциометрии. Общая модель дифференциального обратного сигнала инверсии рассматривается в виде полинома линейно независимых функций, аппроксимирующих отдельные компоненты, расположенные с незначительным взаимным наложением на кривой нижней огибающей. Использование метода моделирования позволяет увеличить точность, повторяемость и надежность определения концентрации за счет устранения субъективных факторов при обработке сигналов. Вперше описано метод моделювання багатокомпонентних сигналів при визначенні концентрації хімічних елементів у хронопотенціометрії. Загальна модель диференційного зворотного сигналу інверсії розглядається у вигляді полінома лінійно незалежних функцій, що апроксимують окремі компоненти, розташовані з незначним взаємним накладенням на кривій нижньої обвідної. Використання методу моделювання дозволяє збільшити точність, повторюваність та надійність визначення концентрації за рахунок усунення суб’єктивних факторів при обробці сигналів. The purpose of the article is to develop a method of modelling multicomponent signals, provided that the spectra is spaced apart and the overlap of the spectral components is small. Methods. Preliminary determination of the parameters of the approximation of the individual spectral components and the base curve is performed. An iterative model of the multi-component signal is sought in the form of generalized polynomial of linearly independent functions by least squares method. At a negative value approximation coefficient corresponding spectral component is considered to be erroneous or not. Results. In the given example the use of the modelling method has allowed to reduce relative error in determining the concentration of copper from 18,9% to 1,5%, compared to the conventional analysis.